Associations of Parental Warmth with Substance Use in the Offspring: A Meta-Analysis. - Pinquart, Martin; Gochaliyev, Zaka (International Journal of Mental Health & Addiction, 2026)
The present meta-analysis examined the relationship between parental warmth and substance use in adolescents and emerging adults. A systematic search of electronic databases identified 319 studies, which were included in a hierarchical random-effects meta-analysis. We found small bivariate associations, as well as very small but statistically significant effects of initial warmth on changes in substance use and of initial substance use on changes in warmth. Bivariate associations were weaker for alcohol than for nicotine and overall consumption of mostly illegal drugs. Stronger bivariate associations were found when child reports on parenting, rather than parental self-reports, were used. Additionally, bivariate associations were weaker in more recent studies. However, the results did not vary by child age or the gender of either the child or the parent. We conclude that promoting parental warmth should be included in parenting training programs aimed at preventing and reducing youth substance use.